Toward the preparation of the HAuF6, HAu2F11, and HAu3F16 superacids: Theoretical study. Issue 4 (25th September 2017) - Czapla, Marcin; Skurski, Piotr
Abstract: We apply the B3LYP and QCISD theoretical methods with the 6‐311++G(d, p) basis set and the LANL2DZ effective core potentials to investigate the reaction paths leading to the preparation of the HAuF6, HAu2 F11, and HAu3 F16 superacids. The Gibbs free energies of deprotonation of these systems are calculated to estimate their acid strength. The thermodynamic stability of the corresponding anionic precursors ((AuF6 ) –, (Au2 F11 ) –, and (Au3 F16 ) – ) and their vertical excess electron detachment energies are evaluated and discussed. The suggested route of the HAu2 F11 preparation involves the F – attachment to the Au2 F10 reactant which results in the formation of the (Au2 F11 ) – anion whose protonation yields the HAu2 F11 superacid. The suggested HAuF6 superacid preparation route is based on a qualitatively similar scheme and involves the conversion of the AuF5 reactant into the (AuF6 ) – anion followed by its protonation. The proposed path for the HAu3 F16 superacid preparation involves the attachment of AuF5 to HAu2 F11 . Abstract : The preparation of HAuF6, HAu2 F11, HAu3 F16 superacids remains unaccomplished due to the instability of their precursors. The suggested route leading to the the HAu2 F11 preparation involves the F – attachment to the Au2 F10 reactant followed by the protonation of the resulting (Au2 F11 ) – anion. The suggested path for HAuF6 preparation involves the AuF5 reactant conversion to the (AuF6 ) – anion followed by its protonation. The HAu3 F16 superacid is proposed to be accessible via the attachment of AuF5 to HAu2 F11 .